An examination of high-speed aircraft – Part 2: Safety and reliability - Luke Pollock; Graham Wild (Transportation Engineering)
This paper presents a detailed accident investigation into incidents involving high-speed vehicles, particularly supersonic and hypersonic platforms. Examining challenges related to engine performance, structural integrity, and economic aspects in military aerospace, the study emphasizes the importance of real-time health monitoring systems. A key highlight is the exploration of how these systems support the autonomy of hypersonic vehicle. While recognizing challenges related to sensitive technologies and data, the paper outlines research directions encompassing human factors, simulation and training programs, and policy advocacy for integrating high-speed aircraft into existing airspaces. In summary, this research contributes valuable insights to the understanding of high-speed aviation accidents, with implications for improving safety and efficiency in the future and ultimately shows that high-speed aviation safety cannot be treated in the same manner as its subsonic counterpart.